Emergency Surgical Airway Model for Procedural Skills Simulation - Jason Stopyra; Jonah Gunalda; Cedric Lefebvre; David Manthey (eScholarship Publishing, University of California, 2017)
Audience: Medical Students, Interns, Residents, Fellows and Attending Physicians. Introduction: Most residents graduate residency without having the opportunity to perform emergency cricothyrotomy in a real failed airway scenario. Simulation training is therefore often utilized to fulfill residents' procedural education. Animal tracheas are common models, but there is difficulty maintaining the unattached trachea in appropriate alignment and exposure. This manuscript outlines the materials and steps to reproduce a realistic, reusable cricothyrotomy simulation model and utilize it in training. Methods: Supplies from a local hardware store plus beginner woodworking skills and tools were used to build a pig trachea holding device. This simulation model has been used by the site's Emergency Medicine residents as a tool for procedural airway training since 2011. Results: The pig trachea simulation model has become a reusable, favorable tool and permanent part of resident skills training sessions, which are held at the beginning of every academic year. A survey was administered which revealed that the model was easy to use, was a good simulation, and improved residents' comfort level performing a cricothyrotomy. Conclusion: The inexpensive, reusable surgical airway model using a pig trachea holder and cadaveric skin is a useful, high fidelity procedural training tool. It has successfully fulfilled trainees' need to practice this rare but potentially life-saving procedure.